Studies on Secondary Metabolites and In vitro and In silico Anticholinesterases Activities of the Sea Urchin Echinometra mathaei Crude Venoms from the Persian Gulf-Bushehr - Dehghani, Hamideh; Rashedinia, Marzieh; Mohebbi, Gholamhossein; Vazirizadeh, Amir (Natural Products Journal, The, 2024)
Background: Echinoderms are a unique source of amazing secondary metabolites with a wide spectrum of biological activities. Several species of sea urchins contain various toxins and biologically active metabolites. One of the most attractive approaches to treat Alzheimer's disease is searching for effective marine natural products with cholinesterase inhibitory activities. Objective: The current study is designed to investigate the in vitro and in silico acetylcholinesterase and butyrylcholinesterase inhibitory activities of the Persian Gulf echinoderm sea urchin Echinometra mathaei venom and related chemical compounds. Methods: The experiments for LD50, total protein, protein bands, in vitro cholinesterase inhibitory activities, the identity of secondary metabolites, and the in silico evaluations, respectively, were performed by Spearman-Karber, Lowry, SDS-PAGE, Ellman's spectroscopic, GC-MS, and docking methods. Results: The LD50 (IV rat) of the spine, gonad, and coelomic fluid from sea urchin samples were 2.231 ± 0.09, 1.03 ± 0.05, and 1.12 ± 0.13 mg/ml, respectively. The SDS-PAGE and total protein studies showed that at least a portion of the venom is protein in nature. GC-MS analysis of the identified samples revealed 12, 23, and 21 compounds with different chemical types, including alkaloids, terpenes, and steroids, respectively. According to the results, all samples act as significant inhibitors of both enzymes. In silico data for the identified compounds also confirmed the experimental results. Conclusion: The alkaloid compound 6H-Indolo[3,2,1-de] [1,5] naphthyridine-6-one,1,2,3a,4,5- hexahydro-8-hydroxy-3-methyl (C7 ) had the highest affinity for both enzymes. Further research is needed to determine whether C7 could be a therapeutic candidate for Alzheimer's disease.
Keywords: alzheimer’s disease